Interpreting success and failure: the eclectic careers of Eva and Juliette Gauthier - Slominska, Anita (Université McGill, 2009)
My dissertation explores the eclectic singing careers of sisters Eva and Juliette Gauthier. Born in Ottawa, Eva and Juliettte were aided in their musical aspirations by the patronage of Prime Minister Wilfred Laurier and his wife Lady Zoë. They both received classical vocal training in Europe. Eva spent four years in Java. She studied the local music, which later became incorporated into her concert repertoire in North America. She went on to become a leading interpreter of modern art song. Juliette became a performer of Canadian folk music in Canada, the United States and Europe, aiming to reproduce folk music “realistically” in a concert setting. My dissertation is the result of examining archival materials pertaining to their careers, combined with research into the various social and cultural worlds they traversed. Eva and Juliette’s careers are revealing of a period of transition in the arts and in social experience more generally. These transitions are related to the exploitation of non-Western people, uses of the “folk,” and the emergence of a cultural marketplace that was defined by a mixture of highbrow institutions and mass culture industries. My methodology draws from the sociology of art and cultural history, transposing Eva and Juliette Gauthier against the backdrop of the social, cultural and economic conditions that shaped their career trajectories and made them possible.

« Un studio à soi ». Entrevue avec Bérengère Marin Dubuard, du Studio XX - Parent, Sylvie (ETC, 2008)
Un article de la revue ETC, diffusée par la plateforme Érudit.

Un entretien avec Diane Labrosse - Cornell, Andrea-Jane (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
This interview with Diane Labrosse was conducted in December 2004 in the offices of Production SuperMusique within the framework of Dr. Andra McCartney's In and Out Of the Sound Studio project. Andrea Jane Cornell asked Labrosse about the experiences that brought her to choose sound as a medium for her artistic expression, and the methods that she employs to create sound.

Gender, Genre and Electroacoustic Soundmaking Practices - McCartney, Andra (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
This article is an exploration of how genres and practices of electroacoustic soundmaking are gendered, examining processes of gendering in language used in the early dichotomous categorization between musique concrète and elektronische Musik, then thinking about related arguments concerning abstraction, context, and compositional control in the writings of electroacoustic soundmakers including Pierre Schaeffer, Pierre Boulez, Daphne Oram, Pauline Oliveros, and several participants of the In and Out of the Sound Studio project. Analysis of their practices and ideas suggests different ways of conceptualising electroacoustic genres, their related practices, and roles of contemporary electroacoustic soundmakers (composers, artists, producers, mixers, audiences...), by examining the potentials of the concepts of empathetic knowledge and ecological thinking advanced by feminist epistemologist Lorraine Code.

In and Out of the Sound Studio: Introduction - McCartney, Andra; Waterman, Ellen (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
Dans l’introduction à ce numéro spécial d’Intersections, Andra McCartney et Ellen Waterman présentent les Dedans et Dehors du Studio, un projet de recherche ethnographique inter-universitaire soutenu financièrement par le CRSH du Canada de 2001 à 2005. L’équipe de recherche a étudié les idées et pratiques des artisans sonores canadiens, se penchant particulièrement sur le sujet de la relative invisibilité et inaudibilité des femmes, réfléchissant aux différentes manières dont les technologies et pratiques sonores peuvent être orientées sexuellement. Dans leurs essais, les auteures discutent des relations trouvées entre les termes genre, son et technologie, du point de vue aussi bien terminologique, qu’esthétique, du mentorat, ou encore méthodologique et théorique. Les contributions de McCartney, Diamond, Laplante, Labrosse, Marsh et Bosma sont ici discutées.

C'était du spectacle! L'histoire des artistes transsexuelles à Montréal, 1955-1985 - Namaste, Viviane (McGill-Queen's University Press, 2005)
Le quartier chaud de Montréal a fait couler beaucoup d'encre, mais sa culture de cabaret n'a jamais été examinée dans la perspective des artistes transsexuelles et travesties qui l'ont rendu si populaire. Par le biais des récits provenant des danseuses elles-mêmes, Viviane Namaste peint un portrait honnête de quatorze transsexuelles - danseuses, chanteuses, magiciennes ou effeuilleuses - et jette un regard dans les coulisses du monde dans lequel vivent et travaillent ces hommes devenus femmes. Les années soixante et soixante-dix ont été des décennies de changement social au Québec. C'était du spectacle! raconte l'histoire de la première génération de transsexuelles ayant subi une chirurgie d'inversion de sexe. Namaste examine les conditions de travail dans les cabarets, la prostitution, les abus de pouvoir des policiers à l'égard des transsexuelles, le rôle du crime organisé dans la vie nocturne de la ville et l'accès aux soins de la santé. C'était du spectacle! offre un rare survol de la culture urbaine de Montréal, présenté dans ses propres mots par l'une de ses plus importantes communautés artistiques.

Considering Complexity in Canadian Civil Society: A Case Study of Studio XX - Gerlach, Neil; Hamilton, Sheryl (Revista Mexicana de Estudios Canadienses, 2002)

Virtually Civil: Studio XX, Feminist Voices, and Digital Technology in Canadian Civil Society - Gerlach, Neil; Hamilton, Sheryl N. (Civic Discourse and Cultural Politics in Canada, 2002)

New Games in the Digital Playground: Women Composers Learning and Teaching Electroacoustic Music - McCartney, Andra (Feminism & Psychology, 2002)

Québec, vingtième siècle : La création musicale, une affaire de femmes ? - Galaise, Sophie (Musicanada 2000: A Celebration of Canadian Composers/Un hommage aux compositeurs canadiens, 2001)